Function and evolution of microRNAs in eusocial Hymenoptera - Søvik, Eirik; Bloch, Guy; Ben-Shahar, Yehuda (Frontiers in Genetics, 2015)
The emergence of eusociality (“true sociality”) in several insect lineages represents one of the most successful evolutionary adaptations in the animal kingdom in terms of species richness and global biomass. In contrast to solitary insects, eusocial insects evolved a set of unique behavioral and physiological traits such as reproductive division of labor and cooperative brood care, which likely played a major role in their ecological success. The molecular mechanisms that support the social regulation of behavior in eusocial insects, and their evolution, are mostly unknown. The recent whole-genome sequencing of several eusocial insect species set the stage for deciphering the molecular and genetic bases of eusociality, and the possible evolutionary modifications that led to it. Studies of mRNA expression patterns in the brains of diverse eusocial insect species have indicated that specific social behavioral states of individual workers and queens are often associated with particular tissue-specific transcriptional profiles. Here we discuss recent findings that highlight the role of non-coding microRNAs (miRNAs) in modulating traits associated with reproductive and behavioral divisions of labor in eusocial insects. We provide bioinformatic and phylogenetic data, which suggest that some Hymenoptera-specific miRNA may have contributed to the evolution of traits important for the evolution of eusociality in this group.